PERAN TOKOH MASYARAKAT DALAM PENGAWASAN TERHADAP PEREDARAN MINUMAN BERALKOHOL TRADISONAL DI KELURAHAN RUM, KOTA TIDORE KEPULAUAN - Putri Faturahman Ismail; Abdurrahaman Kader (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2023)
Abstract In general, the purpose of this study is the role of community leaders in the supervision of the circulation of traditional alcoholic beverages in Rum Village, Tidore Archipelago City. The research method used is qualitative descriptrify. The data analysis technique used is an interactive model. The results showed that the circulation of traditional alcoholic beverages in Rum Village was not controlled, which caused teenagers or young people to easily get it. The bad impact is the emergence of various societal diseases such as, fights, disrupting public order, and making a fuss. To overcome the problem is to involve community leaders, because community leaders are respected people in the community. However, the Rum Village Government has not maximized the role of community leaders in the supervision of the circulation of traditional alcoholic beverages in its territory.